Training and Development in Employee Retention and Organizational Effectiveness at a Manufacturing Firm in Naga City, Cebu, Philippines - Tabasa, Chester S.; Polinar, Mark Anthony N.; Delantar, Alexander Franco A.; Delantar, Allan B.; Ouano, Celso L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This descriptive-correlational study investigates the relationship between training and development, employee retention, and organizational effectiveness within a manufacturing firm in Naga, Cebu, Philippines. Three hundred sixty respondents were selected randomly to participate in the study, utilizing a validated and reliable questionnaire to collect pertinent data. The findings, analyzed using Spearman's rho, indicate a significant correlation between training and development, employee retention, and organizational effectiveness. Furthermore, simple linear regression analysis demonstrates that training and development correlate and serve as predictors of employee retention and organizational effectiveness. This emphasizes the importance of implementing comprehensive training and development programs that significantly boost employee retention and improve overall organizational effectiveness. Such initiatives are essential not only for fostering individual growth and skill enhancement but also for aligning with strategic human resource planning, ensuring that the workforce is equipped to meet current and future challenges. Accordingly, it is concluded that training and development should be viewed not merely as supplementary efforts but as essential components of a comprehensive business strategy, which contribute significantly to organizational success. Implementing an employee-centered training program fosters employee engagement, empowerment, and a sense of purpose.